INVESTIGATION OF ACADEMIC SELF-EFFICACY ACCORDING TOPERCEPTIONS OF SPORTS HIGH SCHOOL STUDENTS - Bingölbalı, Abdullah; Karakaya, Yunus Emre (My University, 2021)
This study aims to investigate academic self-efficacy according to the perceptions of students who studied in sports high schools. The study covered a sample of 538 students, who were randomly chosen and studied in Elazığ Sports High School, Malatya Sports High School, and Mardin Sports High School. The data were collected from the sample of the study by using the “Academic Self-Efficacy Scale”. The data were analyzed by using the licensed SPSS 22.0 package software. The Cronbach alpha coefficient of the scale was calculated as 0.82. As a result of the investigations, in the education period, statistically significant differences were determined according to the variable of the place of residence. No differences were observed in terms of the variables of gender, grade level of education, and family’s monthly income level. In conclusion, supporting academic self-efficacy in sports high school students, especially developing academic planning skills, can contribute to reducing academic procrastination behaviors. In both educational and other guidance activities to be held in these educational institutions, studies that emphasize improving the academic self-efficacy of students can be conducted. Additionally, conducting similar studies can further contribute to the comprehension of the concept by including qualitative data collection processes such as open-ended questions.
Keywords: Eğitim; Eğitim Araştırmaları; Spor Bilimleri